Treatment of pineal region lesions : our experience in 39 patients - Sajko, Tomislav (Array, 2009)
Abstract: The pineal region is the origin of lesions with a highly diverse histopathology. The aim of this study was to present our experience in treating patients with the pineal region lesions. In period between 1990 and 2007, 39 patients with pineal region lesions were operated on at the Department of Neurosurgery, University Hospital »Sestre milosrdnice«, Zagreb, Croatia. The study group consisted of 21 female and 18 male patients with the median age of 24.4 years (4–66 years). Surgery was performed using the infratentorial supracerebellar approach in all patients. The pineal region lesions were removed totally in 23 (58.97%), subtotal in 14 (35.9%) and partially in 2 (5.13%) patients. Pathohistological examination revealed 13 pineocytomas (33.33%), 10 germinomas (25.64%), 7 glial cysts (17.94%), 3 pineoblastomas (7.69%), two pilocytic astrocytomas (7.69%) and one case (2.56%) of papilloma plexus chorioideus, epidermal cyst, yolk sack tumor and ganglioglioma. There was no surgical mortality. Thirteen patients (33.3%) experienced complications in the postoperative period. During the follow-up period that ranged from 3 to 48 months six patients died (15.4%). The infratentorial supracerebellar approach is a safe and effective surgical approach. Benign pineal lesions could be cured with surgery alone. In the case of malignant pineal lesions radical surgical resection allowed determining the exact pathohistological diagnosis and facilitated adjuvant therapy (irradiation and chemotherapy)